Validation of the Hospitality Culture Scale in the Context of Hotel Industry - Fernandes, A.; Alturas, B.; Laureano, Raul M. S. (TMS ALGARVE 2016 – Tourism & Management Studies International Conference, 2016)
This study aims to validate the final factors for the Organizational Culture of the Hospitality Culture Scale which consists of the following four dimensions: management principles, customer relationships, job variety, and job satisfaction in the context of hotel industry organizations both in Brazil and Portugal. To this end, a confirmatory factor analysis (CFA) was performed, where two hundred and fifty-nine hotel industry’s professionals were rated. The presented results support a structure with three factors and eighteen items. It was concluded that the factor "job satisfaction" does not contribute to the formation of the OC construct. It is understood that an appropriate OC to the hospitality environment can make employees feel valued, which can impact job satisfaction, but job satisfaction cannot be considered part of the values shared by members of an organization.